Chemical Separation of Fixed Tissue Using Thermolysin. (31st July 2013) - Dua, Anahita; Desai, Sapan S.
Abstract : Thermolysin is a metallopeptidase used to cleave peptide bonds at specific junctions. It has previously been used to cleave specific amino acid sequences found at the junction of the sensory epithelium and underlying stroma of unfixed otolithic organs of the vestibular system. We have used thermolysin to separate sensory epithelium from the underlying stroma in fixed cristae ampullares of mouse, rat, gerbil, guinea pig, chinchilla, and tree squirrel, thus removing the saddle-shaped curvature of the sensory organ and creating a flattened sensory epithelium preparation. This permits visualization of the entire sensory organ in a single mount and facilitates proper morphometric analysis.